The Dynamic Evolution of International Environmental Law - Scott, Karen N (Victoria University of Wellington Law Review, 2018)
This article will explore selected innovations within multilateral environmental agreements that have contributed to the dynamic evolution of international environmental law within the context of the traditional rules relating to treaties, international institutions and state responsibility. It will argue that whilst these innovations undoubtedly push and develop the boundaries of these areas of law, they do not represent a significant departure from the traditional principle of consent that underpins international law more generally. But should they? The period of modern international environmental law (from 1972 to date), which from a lawyer's perspective might be described as dynamic and innovative, has simultaneously witnessed significant and persistent environmental change and degradation across the biosphere, atmosphere and hydrosphere. The question for 21st century environmental lawyers is whether international environmental law is fit for the Anthropocene and whether there is sufficient scope for future dynamic evolution within the constraints and structures of the existing international legal system.